Analysis of Public Service Professionalism at the Department of Population and Civil Registration Ambon City - Zainal Abidin Rengifurwarin (GoAcademica Research & Publishing, 2020)
Public services by local government officials are currently required to be carried out professionally is a tough task to improve the expected quality. In reality, the service quality has not been satisfactory, including at the Ambon City Population and Civil Registry Service (Hereinafter known as DISDUKCAPIL). This research aims to analyze and explain the description of how the quality of public services in this department, and the dimensions of employee service professionalism, are determinants of support and obstacles. The number of informants in this research was 11 people. The research data were collected through interview techniques, observation and documentation, and analyzed using qualitative descriptive analysis techniques. The findings of this research indicate that the level of service quality in the field of population administration at the research location is in quite good condition. This is a contribution from several dimensions of the professionalism of employees' work.